Morphological study of the urotergite I process in ten species of the genus Triatoma (Hemiptera, Reduviidae, Triatominae) - Osório-Quintero, Lisardo; Ceretti, Walter; Vendrami, Daniel Pagotto; da Rosa, João Aristeu [UNESP]; de Oliveira, Jader [UNESP]; Obara, Marcos Takashi; Barata, José Maria Soares (Elsevier, 2019)
The insects of subfamily Triatominae exhibit many morphological features used for taxonomic identification. In some species, however, these features are very similar. The authors have proposed by first time the description of the structure referred as urotergite I process. The objective of the study was analyse the use of urotergite I process in the species of the genus Triatoma as a taxonomic feature that may contribute to the more precise and correct identification of these Trypanosoma cruzi Chagas, 1909 vectors. Scanning electron microscopy (SEM) was used to describe the structure of urotergite I process in ten Triatoma (Hemiptera, Reduviidae, Triatominae) species: Triatoma brasiliensis Neiva, 1911; Triatoma circummaculata Stål, 1859; Triatoma infestans (Klug, 1834); Triatoma maculata (Erichson, 1848); Triatoma pseudomaculata Corrêa & Espínola, 1964; Triatoma rubrovaria (Blanchard, 1843); Triatoma sordida (Stål, 1859); Triatoma tibiamaculata (Pinto, 1926); Triatoma vitticeps (Stål, 1859) and Triatoma wygodzinskyi Lent, 1951. The morphological description of the urotergite I process reflects the taxonomic value of the structure for separating and identifying species of ten specimens of the genus Triatoma. The morphological pattern of the urotergite I process on these ten species was compared, and interspecific variability was observed. We suggest the use of the urotergite I process as a complementary character to identify insects of the subfamily Triatominae. In the future, the use of the urotergite I process in dichotomic keys to identify triatomines may contribute to the improvement of the entomological surveillance of Chagas' disease.
Keywords: Chagas disease; Morphology; Taxonomy; Triatominae; Urotergite